Kotti & Co - Å ta protesten til gaten - Kohne, Sara (Tidsskrift for kulturforskning, 2016)
Abstract The potentials of urban public space are often seen as an arena for the representation and articulation of the needs of people with different social and ethnic background, as well as a space for encounter and communication between them. The aim of this paper is to suggest an answer to the question how these potentials are turned to account in the context of fighting for the right to stay. I will approach the question by exploring the activities in public space that were carried out by the initiative Kotti & Co in Berlin Kreuzberg. Being motivated by the need to fight against unaffordable housing and displacement in their neighbourhood, Kotti & Co started in May 2012. The locals managed to occupy part of a public square and to turn it into a permanent protest camp. From here, the activists actu-alize their protest, declare demands, and withstand political strategies that try to assimilate them or tire them out. I argue that the initiative has created an important meeting place for people with different social, political and ethnic backgrounds, as well as a forum for a new and solidary form of public togetherness. These activities have strengthened Kotti & Co’s protest against gentrification of this urban quarter.